ALGUMAS OBSERVAÇÕES SÔBRE O COLEÓPTERO Macrodactylus pumilio BURM., 1855 (SCARABAEIDAE, MELOLONTHINAE) - Junqueira, Guilherme Monteiro (REVISTA DE AGRICULTURA, 2015)
ALGUMAS OBSERVAÇÕES SÔBRE O COLEÓPTERO Macrodactylus pumilio BURM., 1855 (SCARABAEIDAE, MELOLONTHINAE)